Evaluation of a midwifery network to guarantee outpatient postpartum care: a mixed methods study - Susanne Grylka-Baeschlin; Carolina Iglesias; Rebekka Erdin; Jessica Pehlke-Milde (BMC, 2020)
Abstract Background The necessity of outpatient postpartum care has increased due to shorter hospital stays. In a health care system, where postpartum care after hospital discharge must be arranged by families themselves, this can be challenging for those experiencing psychosocial disadvantages. Therefore, we compared characteristics of users of a midwifery network which referred women to outpatient postpartum care providers with those of women organising care themselves. Additionally, we investigated benefits of the network for women and health professionals. Methods Evaluation of the services of a midwifery network in Switzerland. We combined quantitative secondary analysis of routine data of independent midwives with qualitative telephone interviews with users and a focus group with midwives and nurses. Descriptive statistics and logistic regression modelling were done using Stata 13. Content analysis was applied for qualitative data. Results Users of the network were more likely to be: primiparas (OR 1.52, 95% CI [1.31-1.75, p < 0.001]); of foreign nationality (OR 2.36, 95% CI [2.04-2.73], p < 0.001); without professional education (OR 1.89, 95% CI [1.56-2.29] p < 0.001); unemployed (OR 1.28, 95% CI [1.09-1.51], p = 0.002) and have given birth by caesarean section (OR 1.38, 95% CI [1.20-1.59], p < 0.001) compared to women organising care themselves. Furthermore, users had cumulative risk factors for vulnerable transition into parenthood more often (≥ three risk factors: 4.2% vs. 1.5%, p < 0.001). Women appreciate the services provided. The collaboration within the network facilitated work scheduling and the better use of resources for health professionals. Conclusions The network enabled midwives and nurses to reach families who might have struggled to organise postpartum care themselves. It also facilitated the work organisation of health professionals. Networks therefore provide benefits for families and health professionals.